2000
DOI: 10.1046/j.1523-1739.2000.99161.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Isolated Wetland Size, Hydroperiod, and Amphibian Species Richness: Implications for Wetland Regulations

Abstract: Wetland development within the United States is regulated primarily by size. Decisions concerning wetland destruction or conservation are therefore based in part on three inherent assumptions: (1) small wetlands contain water for short portions of the year; (2) small wetlands support few species; and (3) species found in small wetlands are also found in larger wetlands. We tested these assumptions using data on wetland size, relative hydroperiod (drying scores), and relative species richness of amphibians in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
195
3
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(218 citation statements)
references
References 14 publications
14
195
3
6
Order By: Relevance
“…The conservation of wetlands based on its size has been a criterion analysed in the literature (Gibbs, 2000;Snodgrass et al, 2000). Several studies have already highlighted the importance of small wetlands for the conservation of biodiversity (Semlitsch and Bodie, 1998;Russel et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The conservation of wetlands based on its size has been a criterion analysed in the literature (Gibbs, 2000;Snodgrass et al, 2000). Several studies have already highlighted the importance of small wetlands for the conservation of biodiversity (Semlitsch and Bodie, 1998;Russel et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Large open-canopy ponds are associated with higher primary productivity, including high standing crop and diversity of periphyton and macrophytes (Skelly et al 2002), which can be beneficial for amphibians as a refuge from predators and substrate for eggs (Strijbosch 1979). Hydroperiod is another widely cited factor influencing amphibian species richness Aquat Ecol (Snodgrass et al 2000;Skelly 2001;Babbitt, Baber and Tarr 2003;Werner et al 2007a). A number of studies have demonstrated that ponds with intermediate hydroperiod are optimal breeding sites for many amphibian species and thus tend to have high species richness (Wilbur 1980;Werner et al 2007a).…”
Section: Relative Importance Of Metacommunity Processesmentioning
confidence: 99%
“…water depth, salinity; Welborn et al 1996;hydroperiod;Snodgrass et al 2000;number of predators;Van Buskirk 2005;pond size, vegetation;Vági et al 2013) and landscape variables (e.g. forest cover, proportion of open landscape; Van Buskirk 2005;Richter-Boix et al 2007) are both important in shaping amphibian communities.…”
Section: Introductionmentioning
confidence: 99%
“…Higher water levels in consolidated wetlands could mean that those wetlands will need a much more extreme drought to dry out completely, simply because they are larger and deeper. This process changes the wetland from one with fluctuating hydrology to one that is essentially permanently flooded, fundamentally changing the community composition of the wetland and its function in the landscape (van der Valk et al 1994, Wellborn et al 1996, Snodgrass et al 2001.…”
Section: Introductionmentioning
confidence: 99%